Pengetahuan Masyarakat terhadap Pemanfaatan Bambu sebagai Tumbuhan Obat - Yuli Febrianti; Yuni Krisnawati; Reny Dwi Riastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the knowledge and perceptions of the community in the Curug Embun Waterfall area about the use of bamboo as a medicinal plant for the development of medicinal plant programs. The method used is descriptive qualitative through four stages: collecting secondary data in the form of literature studies, field observations, interviews with respondents, taking medicinal plant data, processing and analyzing all data obtained in the previous stage. The results showed that the leaves, stems and roots of bamboo apus or pring tali (Gigantochloa apus), black bamboo or pring wulung (Gigantochloa atroviolacea), bamboo ater or pring ater (Gigantchloa atter), bamboo andong or pring lorek (Gigantochloa pseudoarundinacea), bamboo aor or pring ampel ijo (Bambusa vulgaris), bamboo china or pring fishing (Bambusa multiplex), bamboo betung or pring betung (Dendrocalamus asper), bamboo tamiang or pring flute (Schizostachyum blumei) are used by the community as medicine by boiling and cooking on the frequency of use. As for how to use it to treat various diseases, namely boiling and cooking with the highest frequency of use, namely the apus bamboo species or pring tali (Gigantochloa apus) and Chinese bamboo or fishing rods (Bambusa multiplex) which is 15 with a percentage of 93.75. In conclusion, public knowledge of the types and benefits of bamboo plants as medicinal plants is relatively high. A total of 8 species of bamboo plants have been identified from 4 genera that the public has recognized as medicinal plants. Respondents' perceptions of medicinal plants have a positive effect namely, they consider medicinal plants to be safe for consumption, have no side effects, are cheap, practical, are found in the surrounding environment and feel beneficial for the body. Keywords: Bamboo, Knowledge, Utilization, Perception, Medicinal Plants